2006
DOI: 10.1002/ajh.20804
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemia in chronic anemias with increased erythropoietic activity

Abstract: Hypocholesterolemia of unknown etiology has been previously described in various chronic anemias. Few small studies also suggested that those patients have a lower incidence of atherosclerotic events. The aim of our study was to determine the extent of hypocholesterolemia in various types of anemias. We studied 59 patients with chronic anemias associated with higherythropoietic activity (thalassemia intermedia, congenital dyserythropoietic anemia type I, congenital spherocytosis), 8 patients with low-erythropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 16 publications
(19 reference statements)
5
64
2
1
Order By: Relevance
“…17, It was observed that even though the means of these values were lower than that of the controls, it was still within normal reference interval (2.5-6.5 mmol/l; Table 1). Contrary to previous reports [3][4][5][6]20 only one in five of these patients (20%) had significant hypocholesterolaemia (TC <2.59 mmol/l). The hypocholesterolaemia may be a consequence of increased cholesterol utilization and/or decreased endogenous production.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…17, It was observed that even though the means of these values were lower than that of the controls, it was still within normal reference interval (2.5-6.5 mmol/l; Table 1). Contrary to previous reports [3][4][5][6]20 only one in five of these patients (20%) had significant hypocholesterolaemia (TC <2.59 mmol/l). The hypocholesterolaemia may be a consequence of increased cholesterol utilization and/or decreased endogenous production.…”
Section: Discussioncontrasting
confidence: 96%
“…Hypocholesterolaemia has been described in various anaemias with high erythropoietic activity [1][2][3][4][5][6][7] . In Nigerian children with sickle cell anaemia (SCA) and African-American patients with sickle cell disorder a significant reduction in plasma cholesterol; high density lipoprotein (HDL-c) and low density lipoprotein (LDLc) cholesterol concentration compared to normal controls have been reported 2,3 A study on adult with SCA reported low serum total cholesterol, LDL, HDL as well as lowered BMI compared to their controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the opposing effects of testosterone and estrogens in regulating blood levels of LDL and HDL cholesterol are not a good explanation for the mortality difference in our patients who, overall, tend to have very low levels of total cholesterol. 20 However, the gender difference in survival was already present in a survey performed in 1983, including patients born before 1970, when only a small proportion of patients had spontaneous puberty and very few were receiving hormone replacement therapy. In addition, it has been suggested that women survive longer because they have a slower metabolic rate almost from the moment of conception, when male embryos divide faster than female ones.…”
Section: Proposed Explanationsmentioning
confidence: 99%
“…8 Finally, in a study evaluating hypocholesterolaemia among thalassaemia intermedia patients, a significant inverse correlation was found between cholesterol level and soluble transferrin receptor. 27 Further studies are needed to better elucidate the relationship between…”
Section: Pathogenesismentioning
confidence: 99%